Unpacking Genre-Based Instruction: Cognitive, Emotional, and Behavioral Engagement in High School Writing - Asbar Asbar; Murni Mahmud; Abdul Halim (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2025)
Genre-Based Instruction (GBI) is a structured approach that scaffolds students’ writing development by explicitly teaching genre conventions and guiding them through sequenced instructional stages. This qualitative study explores cognitive, emotional, and behavioral engagement among high school students who have experienced GBI in their writing instruction. This study, conducted at SMAN 1 Enrekang and SMAN 2 Enrekang, employs semi-structured interviews to capture students' lived experiences and perceptions. Using thematic analysis, findings reveal that GBI enhances cognitive engagement by improving genre awareness and structural clarity in writing, while emotional engagement is fostered through increased writing confidence and motivation, particularly in collaborative Joint Construction activities. Behavioral engagement is reflected in students’ active participation, peer interaction, and deeper involvement in the writing process. However, challenges include limited vocabulary acquisition, which hindered comprehension of genre-specific conventions, and time constraints, which restricted students’ ability to internalize writing structures before transitioning to independent tasks. These findings highlight the need for curricular flexibility to accommodate a more reflective writing process, as well as technology-supported vocabulary development to enhance students’ engagement with genre-specific text. While GBI effectively cultivates writing engagement across cognitive, emotional, and behavioral domains, its success depends on instructional refinements and professional development for teachers. Additionally, supportive policy frameworks are crucial to ensuring sustainable and adaptable implementation. This study contributes to ongoing discussions on effective writing pedagogy, offering insights into optimizing GBI for diverse educational contexts.